Predicting OncoDX Recurrence Scores With Immunohistochemical Markers. Issue 1 (January 2015) - Bradshaw, Scott H.; Pidutti, Dale; Gravel, Denis H.; Song, Xinni; Robertson, Susan J.
<x xml:space="preserve">Abstract</x> Recent reports suggest that immunohistochemistry (IHC) markers can be used to give prognostic information in breast cancer that is similar to that contained in the Genomic Health Inc. OncoDX recurrence score (Onco-RS). Our own previous work confirmed that an IHC model based on estrogen receptor (ER), progesterone receptor (PR), and Ki67 predicts 62% of the Onco-RS variability. Other markers used in the Onco-RS include proteins thought to increase tumoral invasive potential, and one such marker is matrix metalloproteinase-11, also called stromelysin 3 (ST3). The goal of this study is to examine the additional value of including ST3 in an IHC-based model that also includes ER, PR, and Ki67 in predicting the Onco-RS, as compared with an IHC model based only on ER, PR, and Ki67 (IHC-RS). The patient population consists of a retrospectively identified cohort of 91 women with ER-positive, HER2neu-negative breast cancer who completed OncoDX testing. Using stepwise multiple regression incorporating Ki67 percentage and semiquantitative ER, PR, and ST3 scores, the ST3 score was not statistically significant.